THE EFFICACY OF GROUP COGNITIVE BEHAVIOUR THERAPY AMONG PATIENTS WITH DEPRESSION IN FEDERAL NEURO-PSYCHIATRIC HOSPITAL, YABA (2015)
Depression is a major psychological disorder which is common among patients in psychiatric hospitals. Cognitive Behavioural Therapy (CBT) has been used as complimentary intervention for depression, its efficacy on group cognitive therapy in Nigeria is yet to be established. This study therefore, examined the efficacy of group CBT in the treatment of depressed patients at the Federal. Neuro psychiatric Hospital, Yaba (FNPHY) Lagos. The cognitive and behavioural theories provided the theoretical basis. This study involved a survey, using cross sectional expost facto an experimental design. A total of 116 clinically diagnosed depressed patients were purposively recruited at the outpatient clinic of FNPHY. A Questionnaire which contained Becks Depressive Inventory-2 (BDI-II) and Centre for Epidemiological studies-Depression Scale (CES-D) were used for the experiment. Forty participants with highest scores on the depression rating scale were randomlyassigned into 4 groups of 10 each. Three of the groups: Individual and Group (I&G), Individual Therapy (IT), Group Therapy (GT) benefitted from psychological intervention while the last was the control (C). The three experimental groups had eight sessions on goals, identification of problems, activity of negative thoughts, correction of irrational beliefs/thoughts, review, evaluation and termination. The control group had no intervention. The four groups were re-assessed after intervention. Data were analysed with one-way analysis of variance (ANOVA), t-test and multiple regression (p<0.05). The mean age was 36±4.38, nineteen of the participants were single (47.5%), twenty-two were male (55%), and twenty-one had secondary education (52.5%).Participants who received GT and IT significantly reported lower scores on depression than the control, (t=-9.489, df=18).Participants who received group CBT significantly reported lower scores on depression than those who did not: t (18)=-2.218, and t(18)=-2.256, for BDI and CES-D respectively. Participants who received IT significantly reported lower scores on depression than those who did not: t (18) =-6.774 and t (18) =-8.316, for BDI and CES-D. Participants who benefited from GT and IT significantly reported lower score on depression than those who received only GCBT on CES-D t (18) =-4.979. Age, sex, marital and educational status did not predict depression among the participants. Combined Group and Individual Cognitive Behaviour Therapy produced higher efficacy in the treatment of depression. Group and Individual Cognitive Behaviour Therapy may be encouraged for the management for depression